ChemInform Abstract: A Green One‐Pot Synthesis of N‐Alkyl‐2‐(2‐oxoazepan‐1‐yl)‐2‐arylacetamide Derivatives via an Ugi Four‐Center, Three‐Component Reaction in Water. Issue 14 (20th March 2013) - Rasouli, Mohammad Ali; Mahdavi, Mohammad; Ranjbar, Parviz Rashidi; Saeedi, Mina; Shafiee, Abbas; Foroumadi, Alireza
Abstract The highly functionalized heterocyclic system is readily available in the absence of any catalyst.